Christian Eschatology and the Physical Universe - Wilkinson, David (2010)
Does matter matter? The scientific picture of the end of the physical Universe has undergone dramatic changes since the turn of the 21st century, with its future characterized by accelerated expansion and futility. Yet Christian theology has been largely silent on this, despite the interest in eschatology in popular culture and in theology itself. What can Christian theology learn from and contribute to the scientific picture of the future of the Universe? Can the biblical narratives of creation and new creation have a fruitful dialogue with scientific discoveries? David Wilkinson shows what a fruitful dialogue this can be. Critiquing the folk eschatology of the Left Behind series, the misguided faith of the scientific optimists and the lack of scientific engagement of the theologians of hope, Wilkinson argues for a rediscovery of the theological theme of new creation and the centrality of bodily resurrection.
EPrint Processing Status: Author unable to supply full text